2018
DOI: 10.3389/fimmu.2018.00270
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Modulation in Macrophage Effector Function

Abstract: Traditionally cellular respiration or metabolism has been viewed as catabolic and anabolic pathways generating energy and biosynthetic precursors required for growth and general cellular maintenance. However, growing literature provides evidence of a much broader role for metabolic reactions and processes in controlling immunological effector functions. Much of this research into immunometabolism has focused on macrophages, cells that are central in pro- as well as anti-inflammatory responses—responses that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
231
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(245 citation statements)
references
References 160 publications
6
231
3
5
Order By: Relevance
“…M2 macrophages prefer mitochondrial respiration, thus we performed mitochondrial stress assays in untreated macrophages (M0‐Ctr), M2 macrophages (M2‐Ctr) as well as dPGS treated macrophages (M2‐dPGS‐24h; M2‐dPGS‐7d). As described in other studies, anti‐inflammatory macrophages showed a significantly reinforced mitochondrial respiration (as indicated by OCR) ( Figure 5 A) . In contrast, dPGS treatment comprehensively decreased the mitochondrial function within the macrophages.…”
supporting
confidence: 83%
“…M2 macrophages prefer mitochondrial respiration, thus we performed mitochondrial stress assays in untreated macrophages (M0‐Ctr), M2 macrophages (M2‐Ctr) as well as dPGS treated macrophages (M2‐dPGS‐24h; M2‐dPGS‐7d). As described in other studies, anti‐inflammatory macrophages showed a significantly reinforced mitochondrial respiration (as indicated by OCR) ( Figure 5 A) . In contrast, dPGS treatment comprehensively decreased the mitochondrial function within the macrophages.…”
supporting
confidence: 83%
“…In the last decade, a large number of studies showed that M s when activated shift their metabolism from oxidative phosphorylation to aerobic glycolysis. 127,129,132 This change in intracellular metabolism also happens in tumor cells. 133 This phenomenon is called the Warburg Effect.…”
Section: Leptin and The Adipose Tissuementioning
confidence: 97%
“…In addition, M1 and M2 Mϕs are also distinctive metabolically. In the last decade, a large number of studies showed that Mϕs when activated shift their metabolism from oxidative phosphorylation to aerobic glycolysis . This change in intracellular metabolism also happens in tumor cells .…”
Section: Mϕ Metabolism—an Overviewmentioning
confidence: 99%
“…Blocking oxidative metabolism abrogates anti-inflammatory macrophage function without affecting the proinflammatory state (Ghesquiere, Wong, Kuchnio, & Carmeliet, 2014). For a detailed description of both classical and emerging pathways, including metabolic pathways, relevant for macrophage phenotypes we refer the readers to recent excellent reviews (Amici et al, 2017;Diskin & Palsson-McDermott, 2018).…”
Section: Introductionmentioning
confidence: 99%